The expression and characterization of functionally active soluble CD83 by Pichia pastoris using high-density fermentation. - Yugang Guo; Rui Li; Xiaoping Song; Yongjun Zhong; Chenguang Wang; Hao Jia; Lidan Wu; Dong Wang; Fang Fang; Jiajia Ma; Wenyao Kang; Jie Sun; et al. (PLoS ONE)
CD83 is a highly glycosylated type I transmembrane glycoprotein that belongs to the immunoglobulin superfamily. CD83 is upregulated during dendritic cell (DC) maturation, which is critical for the initiation of adaptive immune responses. The soluble isoform of CD83 (sCD83) is encoded by alternative splicing from full-length CD83 mRNA and inhibits DC maturation, which suggests that sCD83 acts as a potential immune suppressor. In this study, we developed a sound strategy to express functional sCD83 from Pichia pastoris in extremely high-density fermentation. Purified sCD83 was expressed as a monomer at a yield of more than 200 mg/L and contained N-linked glycosylation sites that were characterized by PNGase F digestion. In vitro tests indicated that recombinant sCD83 bound to its putative counterpart on monocytes and specifically blocked the binding of anti-CD83 antibodies to cell surface CD83 on DCs. Moreover, sCD83 from yeast significantly suppressed ConA-stimulated PBMC proliferation. Therefore, sCD83 that was expressed from the P. pastoris was functionally active and may be used for in vivo and in vitro studies as well as future clinical applications.